Growth, carcass and meat quality traits of straightbred and crossbred Botucatu rabbits - Bianospino, E.; Wechsler, F. S.; Fernandes, S.; Roça, Roberto de Oliveira [UNESP]; Moura, A. S. A. M. T. (Universidad Politecnica de Valencia, 2006)
The objective was to evaluate the effects of genetic group and age on growth, carcass, and meat traits of rabbits. A total of 144 straightbred Botucatu and White German Giant x Botucatu crossbred rabbits were involved. Rabbits were weaned at 35 d and sequentially, slaughtered, four per genetic group x sex combination, at: 42, 49, 56, 63, 70, 77, 84 and 91 d. A 2x2 factorial arrangement was employed in a completely randomized design with repeated measures for growth traits, and a split-plot for carcass and meat traits. Crossbred rabbits were heavier (2032 vs. 1962 g; P < 0.01), consumed more feed (143.5 vs. 131.0 g/d; P < 0.01), and presented higher slaughter weight (2169 vs. 2093 g, P=0.02) and dressing percentage (59.0 vs. 58.2%; P=0.07) than straightbreds throughout the experiment. No difference between genetic groups was detected for feed conversion and empty gastrointestinal weight corrected for slaughter weight (SW). Crossbreds showed higher skin weight (308.2 vs. 299.7 g, P = 0.06) and distal parts of leg weight (75.7 vs. 71.4 g; P < 0.01), both corrected for SW. No genetic group effect was detected on dissectible fat and hind part weights. Chilled commercial carcass (1284 vs. 1229 g: P=0.02), chilled reference carcass (1036 vs. 1000 g, P=0.06), fore part (297.9 vs. 283.3 g; P=0.01) and loin (308.7 vs. 295.5 g; P=0.05) were heavier in crossbreds than in straightbreds, but these differences were attributed to differences in SW. Uncorrected weights of head, kidneys, liver and thoracic viscera were higher in the crossbred group, but only head (116.6 vs. 113.6 g; P=0.06) and thoracic viscera (30.4 vs. 28.6 g; P=0.01) were, in fact, proportionately heavier in crossbreds than in straightbreds. No effect of genetic group was detected on meat to bone ratio, muscle ultimate pH and chemical composition of the Longissimus dorsi muscle. All traits, except for ash and fat contents of the Longissimus muscle, showed age effects (P < 0.01). Crossbreeding may be recommended for the production of whole commercial carcasses, but it is not clearly advantageous for the production of retail cuts. Slaughter should take place between 63 and 70 d of age for both genetic groups.
Keywords: rabbit; carcass traits; dressing percentage; growth; muscle pHu; retail cuts